PERLINDUNGAN HUKUM TERHADAP TERSANGKA DALAM PENYIDIKAN DARI KEKERASAN PENYIDIK DI KEPOLISIAN RESORT BANYUMAS - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The state has failed to ensure legal protection for investigated suspects from violence committed by the police. Perpetrators of violence in Banyumas Police Resort were left untouched by law. This human rights violations continue to take place because they enjoy protection from their direct supervisors and police institutions.